Effect of Temperature on Removal of Ni(II) from Aqueous Solutions by Adsorption onto Fire Clay - Bajpai, S.K. (Asian Journal of Chemistry, 2010)
The removal of Ni(II) from aqueous solutions by adsorption on fire clay has been studied as a function of temperature. The amount of Ni(II) removed is highly dependent on temperature and favours high temperature, thus showing endothermic nature of the process. Also the initial concentration of adsorbate affects the extent of adsorption significantly. The various rate parameters of the adsorption process have been determined at different temperatures. Activation energy of the process was found to be 34.59 kJ mol–1. The uptake of Ni(II) exhibited Langmuir type adsorption behaviour which was also confirmed by regression analysis. The various thermodynamic parameters have been calculated to reflect the nature of the adsorption process.